Long-Term Climate Trends and Northern Bobwhite Populations in South Texas - Jeffrey J. Lusk; Fred S. Guthery; Markus J. Peterson; Stephen J. DeMaso (National Quail Symposium Proceedings, 2017)
Because climate change and its associated weather changes may influence population trends of birds, we analyzed northern bobwhite (Colinus virginianus; bobwhite hereafter) age ratios and abundance in relation to climate trends during 1908-1997 in south Texas. Weather variables included regional mean temperature maxima for June, July, and August, and precipitation totals for autumn (Sep-Nov), winter (Dec-Feb), spring (Mar-May), and summer (Jun-Aug). Long-term temporal trends for these weather variables were estimated with a linear regression. Yearly weather data were used to predict bobwhite age ratios (juv/ad in autumn and winter) and abundance between 1908 and 1997 using neural network models. We compared these predictions with data available from various bobwhite surveys in south Texas over the period 1940-1999. Means for daily maximum temperature during summer declined at rates between 1.6 and 2.3°C/century. No temporal trends were detected for seasonal precipitation (1908-1997), age ratios (1940-1999), or abundance (1977-1998). Neural models developed independently to predict bobwhite age ratios and bobwhite abundance from weather data produced predictions that were consistent with each other. Years with high age ratios tended to coincide with or precede years of high abundance.
Keywords: climate trends; Colinus virginianus; northern bobwhite; south Texas